Coexistence of tmexCD3-toprJ1b tigecycline resistance genes with two novel blaVIM-2-carrying and blaOXA-10-carrying transposons in a Pseudomononas asiatica plasmid - Li, Qin; Chen, Qiao; Liang, Shuang; Wang, Wei; Zhang, Bingying; Martín-Rodríguez, Alberto J.; Liang, Qinghua; Zhang, Feiyang; Guo, Ling; Xiong, Xia; Hu, Renjing; Xiang, Li; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Tigecycline and carbapenems are considered the last line of defense against microbial infections. The co-occurrence of resistance genes conferring resistance to both tigecycline and carbapenems in Pseudomononas asiatica was not investigated. Methods P. asiatica A28 was isolated from hospital sewage. Antibiotic susceptibility testing showed resistance to carbapenem and tigecycline. WGS was performed to analyze the antimicrobial resistance genes and genetic characteristics. Plasmid transfer by conjugation was investigated. Plasmid fitness costs were evaluated in Pseudomonas aeruginosa transconjugants including a Galleria mellonella infection model. Results Meropenem and tigecycline resistant P. asiatica A28 carries a 199, 972 bp long plasmid PLA28.4 which harbors seven resistance genes. Sequence analysis showed that the 7113 bp transposon Tn7389 is made up of a class I integron without a 5’CS terminal and a complete tni module flanked by a pair of 25bp insertion repeats. Additionally, the Tn7493 transposon, 20.24 kp long, with a complete 38-bp Tn1403 IR and an incomplete 30-bp Tn1403 IR, is made up of partial skeleton of Tn1403, a class I integron harboring blaOXA-10, and a Tn5563a transposon. Moreover, one tnfxB3-tmexC3.2-tmexD3b-toprJ1b cluster was found in the plasmid and another one in the the chromosome. Furthermore, plasmid PLA28.4 could be conjugated to P. aeruginosa PAO1, with high fitness cost. Discussion A multidrug-resistant plasmid carrying tmexCD3-toprJ1b and two novel transposons carrying blaVIM-2 and blaOXA-10 -resistant genes was found in hospital sewage, increasing the risk of transmission of antibiotic-resistant genes. These finding highlight the necessary of controlling the development and spread of medication resistance requires continuous monitoring and management of resistant microorganisms in hospital sewage.